ANALISIS BIAYA KECELAKAAN LALU LINTAS BERDASARKAN KORBAN KECELAKAAN MENGGUNAKAN METODE GROSS OUTPUT DI KABUPATEN JEMBER - Ganda Surahman; Springfield, Dzackirendy (Jurnal Riset Teknik Sipil dan Sains, 2025)
Traffic accidents in Indonesia continue to increase and remain a major issue in road transportation. Traffic accidents are unexpected incidents on the road involving vehicles, either with or without other road users, resulting in human casualties and/or material losses. The material losses caused by these accidents are referred to as traffic accident costs. This study aims to analyze changes in the number of accidents and calculate the total cost of traffic accidents in Jember Regency. The calculation of accident costs is conducted using the gross output (human capital) method. Data on fatalities (MD), serious injuries (LB), minor injuries (LR), and material losses (KM) from 2018 to 2023 were obtained from the Jember Police Traffic Unit (Satlantas Polres Jember). The analysis results show that the highest increase in the number of accidents occurred in 2022, with a rise of 71.49% compared to 2021. Meanwhile, the largest decline in accidents happened in 2020, with a decrease of 16.78% from 2019. Based on the Gross Output method, the highest cost of traffic accident victims was recorded in 2019, with the Biaya Besar Korban Orang (BBKO) reaching Rp 303,423,395,039.79.